Quantitative Analysis of Game Elements for Game-Based Learning In Grammar Instruction in Secondary Education - Ambar Sari (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
Game-based learning brings new experiences for the educational environment. The trend of using the gamification approach is increasingly in demand at all levels of education, especially for secondary education. This study aims to identify the most relevant gamification elements in secondary education through This qualitative study aimed to identify the most relevant gamification elements for grammar instruction in secondary education. Data were gathered through a Focus Group Discussion (FGD) with eight English teachers, selected based on age and technological experience. The FGD was conducted online via WhatsApp and lasted 1.5 hours. Teachers discussed their awareness and perceptions of game-based learning and evaluated nine gamification elements. The analysis showed that 62.5% of participants were already using gamification in grammar lessons, and 75% believed it was important for student engagement. The most preferred elements were interactive mini-games (30%), point systems (25%), daily challenges (20%), badges (15%), and leaderboards (10%). The study concludes that gamification is a promising strategy to improve grammar learning in secondary classrooms. The results of this study can be used as the basis for further researcher in relation to developing a prototype of a game-based learning system in secondary education with a focus on interaction, rewarding, problem solving, and challenges.